The effect of rehabilitation exercises in improving the range of motion and muscle strength of the muscles working on both sides of the spine for women aged (30-40) years - Imad Khlaif (College of Physical Education and Sport Sciences, 2024)
The research aims to relieve pain among women members of the research sample who suffer from low back pain, improve the muscle strength of the muscles working on both sides of the spine, and improve the range of motion of the spine. The researcher used the experimental method for one experimental group using the method of pre- and post-measurements as an experimental design due to its suitability to the nature and purpose of the research. Then The research sample was chosen intentionally from women with lower back pain, numbering (14) whose ages ranged between (30-40) years. Also, a number of (4) cases were randomly selected from the research community and outside the basic sample as an exploratory sample. The researcher used a rehabilitation program. Proposed for six weeks, the following results were reached:                                                                The use of various methods and methods helps to achieve a greater rate of improvement and in less time and cost. In light of this, the researcher recommends:                                                                                                    Spreading awareness and culture among community members about paying attention to early detection of lower back pain to prevent the injury from worsening to advanced degrees.                                                                                        The research aims to reduce pain among women members of the research sample who suffer from lower back pain, improve the muscle strength of the muscles working on both sides of the spine, and improve the range of motion of the spine. The researcher used the experimental method for one experimental group using the pre- and post-measurement method as an experimental design due to its suitability to the nature and purpose of the research., The research sample was chosen intentionally from (14) women with lower back pain whose ages ranged between (30-40) years. Also, a number of (4) cases were randomly selected from the research community and outside the basic sample as an exploratory sample. The researcher proposed a six-week rehabilitation program. The following results were reached: - The rehabilitation program has a positive effect on the injured members of the experimental group. -The use of various methods and methods in the rehabilitation program, such as a physical therapy program, helps to achieve a greater rate of improvement and at a lower time and cost. In light of this, the researcher recommends: - Spreading awareness and culture among community members about paying attention to early detection of cases of lower back pain to prevent the injury from escalating to advanced degrees.